Simbol Natural dalam Lirik Lagu “Di Manakah Matahariku” Karya Ebid G Ade sebagai Sarana Kreatif Penciptaan Kosakata Baru - M. Hermintoyo M. Hermintoyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Song lyrics are created along with a tone of harmonization. The lyrics of the song as the author’s expression are created by choosing the right and aesthetic words, which fulfill elements of beauty such as poems that have diction, images, rhymes, and rhetorical means. Creative lyricist, such as Ebiet G Ade in the song